Rekonstruksi Manajemen Mutu Pesantren - Agus Yudiawan (IAIN Sorong, 2020)
Pesantren is an institution of education and teaching of Islam in which interaction occurs between kyai or ustadz as a teacher and santri as students. Therefore, professional management should be pursued to pursue superior and modern pesantren. This study aims to understand the concept of sharpening pesantren in marginal society. The method used is a literature study or literature review with several relevant references. The results of the study indicate that the understanding that pesantren is a traditional educational institution with the principle of values-oriented to the problem of divinity, so that its management less attention and more conventional. Implementation of Total Quality Management becomes important to be applied which is generally implemented in a qualified pesantren. Management aspects that can be applied to the scope of the pesantren include using the concept according to Harold Koontz with the POSLC function system (planning, organizing, staff, charismatic leading and controlling). Furthermore, a leader must have a high dedication, breakthrough, good communication, financial considerations, skilled emotions and become a good listener.